The PENGENDALIAN MUTU PENDIDIKAN BERBASIS TEKNOLOGI STUDI KASUS KESENJANGAN ANTARA PERSEPSI PEMANGKU KEPENTINGAN DAN CAPAIAN RAPOR PENDIDIKAN DI SDN 2 BATUNYALA - Hiswandi; Saepul Ashari; Pathurrahman; Abdullah; Basilius Redan Werang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The digital transformation of national education has driven rural elementary schools, including SDN 2 Batunyala, to integrate technology into their quality control processes. However, the extent to which this perceived success aligns with nationally measured quality outcomes remains under-researched. This study aims to describe the utilization of technology in educational quality control at SDN 2 Batunyala and to compare stakeholder perceptions with the 2025 Education Report Card (Rapor Pendidikan) data. A qualitative approach with a single case study design was employed. Data were collected through semi-structured interviews with the principal, teachers, students, and parents, and analyzed using the interactive model of Miles, Huberman, and Saldaña, framed within the Total Quality Management and Technological Pedagogical Content Knowledge (TPACK) frameworks. The findings indicate that technology has been integrated into lesson planning, assessment, supervision, and school-parent communication, with all informant groups expressing positive perceptions regarding its impact on student motivation and engagement. However, the 2025 Education Report Card data revealed a decline in scores across all performance dimensions compared to the previous year, including literacy and numeracy, highlights a discrepancy between process perception and measured outcomes. This study concludes that technology-based quality control in rural elementary schools is more accurately understood as an improvement at the process and experiential levels rather than direct evidence of enhanced standardized learning outcomes. Key words: educational quality control; educational technology; TPACK; Education Report Card; case study